Subversion of a family of antimicrobial proteins by Salmonella enterica - Gerlach, Roman G.; Wittmann, Irene; Heinrich, Lena; Pinkenburg, Olaf; Meyer, Torben; Elpers, Laura; Schmidt, Christiane; Hensel, Michael; Schnare, Markus (Frontiers in Cellular and Infection Microbiology, 2024)
Salmonella enterica is a food-borne pathogen able to cause a wide spectrum of diseases ranging from mild gastroenteritis to systemic infections. During almost all stages of the infection process Salmonella is likely to be exposed to a wide variety of host-derived antimicrobial peptides (AMPs). AMPs are important components of the innate immune response which integrate within the bacterial membrane, thus forming pores which lead ultimately to bacterial killing. In contrast to other AMPs Bactericidal/Permeability-increasing Protein (BPI) displayed only weak bacteriostatic or bactericidal effects towards Salmonella enterica sv. Typhimurium (STM) cultures. Surprisingly, we found that sub-antimicrobial concentrations of BPI fold-containing (BPIF) superfamily members mediated adhesion of STM depending on pre-formed type 1 fimbriae. BPIF proteins directly bind to type 1 fimbriae through mannose-containing oligosaccharide modifications. Fimbriae decorated with BPIF proteins exhibit extended binding specificity, allowing for bacterial adhesion on a greater variety of abiotic and biotic surfaces likely promoting host colonization. Further, fimbriae significantly contributed to the resistance against BPI, probably through sequestration of the AMP before membrane interaction. In conclusion, functional subversion of innate immune proteins of the BPIF family through binding to fimbriae promotes Salmonella virulence by survival of host defense and promotion of host colonization.